Aortic and pulmonary artery calcification: An unusual manifestation of twin-to-twin transfusion syndrome - Sumitra Venkatesh; J Sanyukta; S Jain; S S Prabhu; S Kulkarni (Wolters Kluwer Medknow Publications, 2017)
Twin-to-twin transfusion syndrome (TTTS) at times complicates monochorionic twin gestations, resulting in conditions ranging from discordant sizes to fetal demise of one baby. Various types of cardiac defects have been described in the recipient twin of this syndrome. Isolated great artery calcification, i.e. aortic and pulmonary artery calcification is one such uncommon condition associated with TTTS. Calcification of the walls of great vessels may be due to chronic vascular injury sustained as a result of circulatory volume overload in the recipient twin. It may also cause severe systemic hypertension and cardiomyopathy. An accurate diagnosis is important for an optimal follow-up and appropriate genetic counseling. We report a case of aortic and pulmonary artery calcification in association with TTTS.